Computer Security Is Broken: Can Better Hardware Help Fix It? - Kocher, Paul (Communications of the ACM, 2016)
The author argues that hardware can be used to improve computer security. Topics include the relation of a private key on isolated hardware, the use of secure computation on legacy computing architectures, and the relation of security to the future of the technology industry. Problems with SSL/TLS software security standards are noted.